Similar PTSD symptom networks observed in male and female survivors of military sexual assault: implications for understanding trauma responses - Xu, Bingyu; Blais, Rebecca K.; Cruz, Rick A.; Tannahill, Hallie S. (Frontiers in Psychology, 2024)
Posttraumatic stress disorder (PTSD) is a heterogeneous disorder with no universal symptom presentation. Sex differences in rates of PTSD among military samples are established, such that females are more likely to be diagnosed with PTSD, with severity particularly heightened among females exposed to military sexual assault (MSA). However, limited research has examined the PTSD symptom network structure among MSA survivors and whether it differs by sex. The current study examined global and sex-specific PTSD symptom network structure of PTSD among veterans and service members who were exposed to MSA. Participants were 400 service members/veterans (54% active duty; 50% male) with a history of MSA exposure recruited through Qualtrics. Participants completed an online survey assessing PTSD symptoms. Network analysis was conducted for the full sample to examine the overall symptom structure. Centrality indices revealed apathy to be the most central symptom, followed by irritability, hyperarousal, hypervigilance, and external avoidance. The Network Comparison Test was utilized to examine potential sex differences in network structure and global strength. There were no sex differences in global structure or network strength. Core symptom network structures of PTSD may be similar for males and females following MSA. Though males and females experience notable differences in PTSD, network structure is not among them. Central symptoms, or the potential treatment targets, could be similar for males and females MSA survivors.